Production of Nanocellulose from Kepok Banana Peel Waste Using Acid Hydrolysis Method - Putri, Faradilla Nabila; Manurung, Posman; Suciyati, Sri Wahyu; Karo, Pulung Karo (Departement of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2023)
Research on the production of nanocellulose from kepok banana peel waste has been carried out using the Acid Hydrolysis method with H2SO4 Sulfuric Acid. This study aims to determine the effect of giving H2SO4 on kepok banana peels and the crystal structure and surface morphology of nanocellulose on kepok banana peels. The production of nanocellulose was carried out in three stages: delignification using 10% NaOH, bleaching using 10% H2O2, and isolation of nanocellulose using H2SO4 with various concentrations of 5, 10, 15, and 20%. This research uses X-Ray Diffraction (XRD) and Scanning Electron Microscopy (SEM) as its characterization. The resulting crystallite size ranges from 3.58 to 4.15 nm, producing a lump-like morphological structure.